Meloxicam transdermal delivery: effect of eutectic point on the rate and extent of skin permeation - Mohammadi-Samani, Soliman (Mashhad University of Medical Sciences, 2014)
Objective(s): Drug delivery through the skin can transfer therapeutic levels of drugs for pharmacological effects. Analgesics such as NSAIDs have gastrointestinal side effects and topical dosage forms of these drugs are mainly preferred, especially for local pains. Meloxicam is one of NSAIDs with no topical form in the market. In this research, we attempted to quantify the skin permeation of a meloxicam topical preparation and to show how permeation would be increased by using thymol as an enhancer. The effect of eutectic point of drug and thymol mixture on rate and extent of skin permeation was also studied. Materials and Methods: Different mixtures of thymol and meloxicam (2:8, 4:6, 5:5, 6:4, 8:2) were prepared and their melting point were obtained by differential scanning calorimetry. Then drug permeation was measured using diffusion cells and the Guinea pig skin. Results: Mixtures in ratios 5:5 and 4:6 of meloxicam / thymol showed a new endotherm at 149 and 140°C in DSC thermograms. The permeability of meloxicam from the creams containing 6:4, 5:5 and 4:6 ratios of meloxicam to thymol were 4.71, 15.2, 22.06 µg/cm(2) respectively. This was significantly different from the cream of pure meloxicam (3.76 µg/cm(2)). Conclusion: This study set out to determine that thymol plays as a skin permeation enhancer and increases the meloxicam skin absorption and this enhancement is significant at the eutectic point of drug-enhancer mixture.